Recombinant Duck Enteritis Virus-Vectored Bivalent Vaccine Effectively Protects Against Duck Hepatitis A Virus Infection in Ducks - Yang, Fuchun; Liu, Peng; Li, Xiaohan; Liu, Rui; Gao, Li; Cui, Hongyu; Zhang, Yanping; Liu, Changjun; Qi, Xiaole; Pan, Qing; Liu, Aijing; Wang, Xiaomei; et al. (Frontiers in Microbiology, 2021)
Duck enteritis virus (DEV) and duck hepatitis A virus (DHAV) are prevalent duck pathogens, causing significant economic losses in the duck industry annually. Using a fosmid-based rescue system, we generated two DEV recombinants, rDEV-UL26/27-P13C and rDEV-US7/8-P13C, in which the P1 and 3C genes from DHAV type 3 (DHAV-3) were inserted into the DEV genome between genes UL26 and UL27 or genes US7 and US8. We inserted a self-cleaving 2A-element between P1 and 3C, allowing the production of both proteins from a single open reading frame. P1 and 3C were simultaneously expressed in infected chicken embryo fibroblasts, with no difference in growth kinetics between cells infected with the recombinant viruses and those infected with the parent DEV. Both recombinant viruses induced neutralizing antibodies against DHAV-3 and DEV in ducks. A single dose of the recombinant viruses induced solid protection against lethal DEV challenge and completely prevented DHAV-3 infection as early as 7 days post-vaccination. These recombinant P1- and 3C-expressing DEVs provide potential bivalent vaccines against DEV and DHAV-3 infection in ducks.